Intersection between the need for academic achievement and entrepreneurial intentions in Mexican university students - Sánchez Limón, Mónica Lorena; Ortiz González, David Josué; Sánchez Garza, Miriam Nanyeli (Revista de Ciencias Sociales, 2023)
Entrepreneurship and its evolution from intention have garnered increasing interest in research. Borrayo, Valdez & Delgado (2019), indicate that in Mexico, young people are motivated to undertake entrepreneurial ventures during their university years through education and training. Araya-Pizarro (2020), suggests that entrepreneurial education significantly and positively impacts the intention to undertake. The objective of this study is to determine whether the need for academic achievement as part of this type of education received by university students has a positive influence on their entrepreneurial intentions. Quantitative research with a descriptive, correlational-causal approach was conducted involving a sample of 361 students. Descriptive statistical techniques and simple regression analysis were applied based on tested assumptions. The findings revealed a direct yet weak correlation between the variables. It is concluded that the relationship between the need for academic achievement and entrepreneurial intention is complex and variable, with inconsistent outcomes based on cultural and educational contexts. Although the connection exists, its impact does not entirely explain entrepreneurial motivations, emphasizing the necessity for further research to strengthen this field and explore new areas of study.